New potential biomarkers for early chronic kidney disease diagnosis in patients with different glucose tolerance status - Cassano, Velia; Pelaia, Corrado; Armentaro, Giuseppe; Miceli, Sofia; Tallarico, Valeria; Perini, Daniele Dallimonti; Fiorentino, Vanessa T.; Imbalzano, Egidio; Maio, Raffaele; Succurro, Elena; Hribal, Marta L.; Andreozzi, Francesco; et al. (Frontiers in Endocrinology, 2023)
Background The purpose of the present study was to investigate the role of oxidative stress, platelet activation, and endocan levels in renal dysfunction in normal glucose tolerance (NGT) patients with 1-h plasma glucose values ≥155 mg/dl (NGT ≥ 155), compared to NGT < 155, impaired glucose tolerance (IGT), and type 2 diabetes mellitus (T2DM) newly diagnosed subjects. We enlisted 233 patients subjected to an oral glucose tolerance test (OGTT). Materials and methods The serum levels of platelet activation (glycoprotein VI and sP-selectin), oxidative stress biomarkers (8-isoprostane and Nox-2), and endocan were evaluated using an ELISA test. Results Among NGT < 155 patients and the T2DM group, there was a statistically significant increase in 8-isoprostane (p < 0.0001), Nox-2 (p < 0.0001), glycoprotein VI (p < 0.0001), and sP-selectin (p < 0.0001) serum levels. Higher serum endocan levels were found with the worsening of metabolic profile (p < 0.0001); specifically, NGT ≥ 155 patients presented higher serum endocan values when compared to NGT < 155 patients (p < 0.0001). From the multivariate linear regression analysis, 1-h glucose resulted in the major predictor of estimated glomerular filtration rate (e-GFR) justifying 23.6% of its variation (p < 0.0001); 8-isoprostane and Nox-2 added respectively another 6.0% (p < 0.0001) and 3.2% (p = 0.001). Conclusion Our study confirmed the link between 1-h post-load glucose ≥155 mg/dl during OGTT and the possible increased risk for chronic kidney disease (CKD) in newly diagnosed patients. The novelty is that we demonstrated a progressive increase in oxidative stress, platelet activation, and serum endocan levels with the worsening of metabolic profile, which becomes evident early during the progression of CKD.